Pemimpin Negara dalam Perspektif Hadis-Hadis Siyasah: Analisis Hadis Quraisy dan Non-Quraisy dalam Kaitannya dengan Konteks Kepemimpinan di Indonesia - Aripin Marpaung (Pusat Riset dan Inovasi Nasional, 2026)
This study stems from a classic question in the study of political hadith regarding leadership, specifically the hadith